Contrasting effects of landscape on nest founding and colony success of bumble bees in a mixed‐crop agroecosystem - Kwafo, Richard; Galpern, Paul; Cartar, Ralph V. (Insect conservation and diversity, 2023)
Nest‐founding bumble bee queens search landscapes broadly for a nest site, whose later‐developed workers are constrained to foraging around the nest. Landscape could therefore have different influences on nest site selection and subsequent colony success. Additionally, the density of bumble bees in a landscape reflects the product of their nest density and nest success. To examine separate landscape effects on nest density and success, we examined nest occupancy (reflecting nest density) and colony size (reflecting nest success) using ground‐installed nest boxes placed adjacent to blueberry (Vaccinium corymbosum) fields in the Lower Mainland of British Columbia, Canada. Nest‐searching queens occupied 59% of these boxes. We classified landscapes in a 1.5 km radius of colonies using habitats of a priori relevance to bumble bees: beneficial (i.e. flowering) agriculture, non‐beneficial agriculture (NBA), forest, open semi‐natural, suburban, and their configuration (habitat edge density). Landscape strongly affected nest founding but only weakly affected colony success. Nest founding increased in landscapes with more forest habitat, more open semi‐natural habitat (and little NBA), and more habitat edge (and little NBA). Colony success increased in landscapes with more edge density (and much NBA). Overall, edge habitats enhanced bumble bee populations, but enhancement was conditional: edge increased nest occupation in landscapes with little NBA and nest success in landscapes with a lot of NBA. Populations of crop‐pollinating bumble bees might therefore best be enhanced by locally enhancing nesting: protecting forests, 2D semi‐natural habitats (when flowering crops are uncommon), and edge habitats. Habitats in a blueberry agroecosystem influenced nest founding more than colony success in bumble bees, suggesting that farmers should pay particular attention to local habitats to recruit nesting queens. Nest founding increased with forest and (conditionally) with 2D semi‐natural habitat and habitat edge. Nest success increased (conditionally) with habitat edge. Given that landscape affected nest site selection and nest success differently, studies that set out already‐founded colonies to determine landscape effects on bees seem incomplete.